Breastfeeding during the COVID-19 pandemic: Experience of a Neonatology Unit - Vaz,Ana Sofia (2022)
Abstract Introduction: The novel coronavirus disease (COVID-19) has originated a remarkable global health crisis and posed important challenges to the management of mothers and neonates. The scarcity of robust evidence on the effects of the infection on pregnancy and infants has led clinicians to question long-acquired practices, such as rooming-in and breastfeeding. The authors report the results of the follow-up of neonates born to COVID-19-infected mothers in a level III Neonatology Unit, mainly focusing on the type of feeding implemented. Material and methods: A longitudinal study was performed based on the registry of all cases of infants born to mothers with confirmed SARS-CoV-2 infection during seven months (April 1─October 31, 2020). The institution’s clinical guidance was updated throughout the study period. Obstetric and perinatal data concerning the considered time period were recorded, and follow-up of the mother and child after discharge was performed during the first month through a weekly teleconsultation. Results: Fourteen dyads of SARS-CoV-2-infected mothers and neonates were managed according to the institution’s clinical guidance. At discharge, half of the neonates were breastfed, and half were receiving infant formula (almost all due to initial separation between mother and newborn). At one-month follow-up, 71% of neonates were breastfed, 80% of which exclusively. Discussion: The rates of breastfeeding at discharge were influenced by the institution’s management phase. At one-month follow-up, these rates were below some national data, possibly reflecting difficulties in supporting breastfeeding during the pandemic. Conclusion: The continuous support and promotion of breastfeeding during and after discharge should be a permanent concern of health teams, even in challenging times such as those imposed by the pandemic.